2013
DOI: 10.1155/2013/592821
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Stationary Distribution in a Stochastic SIS Model

Abstract: The dynamics of a stochastic SIS epidemic model is investigated. First, we show that the system admits a unique positive global solution starting from the positive initial value. Then, the long-term asymptotic behavior of the model is studied: whenR0≤1, we show how the solution spirals around the disease-free equilibrium of deterministic system under some conditions; whenR0>1, we show that the stochastic model has a stationary distribution under certain parametric restrictions. In particular, we show that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
(46 reference statements)
1
8
0
Order By: Relevance
“…Remark In the past few decades, lots of researchers have worked on the stationary distribution of stochastic differential equations. () However, the factor of coupling effect on systems has not taken into account, since stochastic coupled systems have wide applications such as biomathematics. Moreover, when the system itself can not achieve a stationary distribution, it is necessary to introduce a response system in order to investigate the synchronized stationary distribution.…”
Section: The Existence Of a Synchronized Stationary Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Remark In the past few decades, lots of researchers have worked on the stationary distribution of stochastic differential equations. () However, the factor of coupling effect on systems has not taken into account, since stochastic coupled systems have wide applications such as biomathematics. Moreover, when the system itself can not achieve a stationary distribution, it is necessary to introduce a response system in order to investigate the synchronized stationary distribution.…”
Section: The Existence Of a Synchronized Stationary Distributionmentioning
confidence: 99%
“…Remark There are some traditional methods to investigate the existence of stationary distribution, such as Hasmiskii's method, Lyapunov method, and so on. Zhao and Zhou et al() investigated the existence of stationary distribution of stochastic competitive models and epidemic models by using Hasmiskii's method. Huang et al used level set method and Lyapunov method to study the issue of steady states.…”
Section: The Existence Of a Synchronized Stationary Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective of this paper is to study the extinction and permanence of the disease in (1). One of popular approaches to the investigation of SIS models is to introduce a reproduction value [32,34]. For example, by defining a threshold R 0 = Λβ/[µ(µ + γ + α)] for system (1) with g(S, I) = SI, Zhou et al [32] obtained the existence of its stationary distribution when R 0 > 1 and found that the disease will go to extinction when either R 0 ≤ 1 or some noise is sufficiently large, i.e., β 2 ≤ 2c 2 (γ+α+µ)+b 2 c 2 .…”
mentioning
confidence: 99%
“…What we are interested in is the existence of stationary distribution and convergence of the population in system (1) in terms of a new threshold, which is different from the basic reproduction number established in [19,27,28,32,34]. For this purpose, we first obtain some estimates of solutions in probability by using some standard inequalities.…”
mentioning
confidence: 99%